Competitive Implications of Cross-Border Banking - Claessens, Stijn (2012)
This paper reviews the recent literature on cross-border banking, with a focus on policy implications. Cross-border banking has increased sharply in recent decades, particularly in the form of entry, and has affected the development of financial systems, access to financial services, and stability. Reviewing the empirical literature, the author finds much, although not uniform, evidence that cross-border banking supports the development of an efficient and stable financial system that offers a wide access to quality financial services at low cost. But as better financial systems have more cross-border banking, the relationship between cross-border banking and competitiveness has to be carefully judged. While developing countries have some special conditions, provided a minimum degree of oversight is in place, they experience effects similar to industrial countries. There are some questions, though, on the effects of cross-border banking on lending based on softer information and on stability. Relevant experiences from capital markets show that the degree of cross-border financial activities can affect local market sustainability and there can be path dependency when opening up to cross-border competition. Reviewing the fast changing landscape of financial services provision, the author argues that cross-border banking highlights the increased importance of competition policy in financial services provision. This competition policy cannot be traditional, institutional based, but will need to resemble that used in other network industries. Furthermore, with globalization accelerating, competition policy will need to be global, supported by greater cross-border institutional collaboration and using the General Agreement on Trade in Services (GATS) process and the disciplines of the World Trade Organization. GATS can be of special value to developing countries as it provides a binding, pro-competition framework that has proven more difficult to establish otherwise.